2002
DOI: 10.1097/00000374-200203000-00007
|View full text |Cite
|
Sign up to set email alerts
|

Paternal Alcohol Exposure Affects Sperm Cytosine Methyltransferase Messenger RNA Levels

Abstract: Alcohol-induced reductions in cytosine methyltransferase mRNA levels may reflect altered genomic imprinting caused by reduced DNA methylation, which, in turn, may lead to the expression of normally silent paternal alleles and may be a mechanism for paternal alcohol effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
53
0
1

Year Published

2003
2003
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(57 citation statements)
references
References 19 publications
3
53
0
1
Order By: Relevance
“…It is reported that 75% of children with fetal alcohol syndrome have fathers who were alcoholics [120]. Alcohol consumption is associated with a deterioration of sperm parameters which may be partially reversible upon alcohol consumption discontinuation [121].…”
Section: Consumption Of Alcoholmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported that 75% of children with fetal alcohol syndrome have fathers who were alcoholics [120]. Alcohol consumption is associated with a deterioration of sperm parameters which may be partially reversible upon alcohol consumption discontinuation [121].…”
Section: Consumption Of Alcoholmentioning
confidence: 99%
“…Testicular deficiency may have different aetiologies and present clinically as severe oligoasthenozoospermic (OAT) or non-obstructive azoospermia (NOA) [120]. In men with testicular deficiency, hypergonadotrophic hypogonadism is usually present, with high levels of follicle-stimulating hormone (FSH) and luteinising hormone (LH), and sometimes low levels of testosterone.…”
Section: Diagnosis and Management For Infertilitymentioning
confidence: 99%
“…Mechanisms postulated for adverse testicular effects are lipid peroxidation (Rosenblum et al, 1985), changes in secretory function of Sertoli cells (Zhu et al, 1997), changes in hormone levels (Woolveridge et al, 1999), and induction of apoptosis (Eid et al, 2002;Hu et al, 2003). Bielawski et al (2002) suggest alcohol may produce transgenerational effects by decreasing cytosine methyltransferase mRNA levels and affecting normal imprinting. Kagan-Krieger et al (2002) suggest paternal alcohol consumption may affect offspring through genetic changes in sperm DNA, decreasing numbers of sperm produced resulting in a less healthy subpopulation available for fertilization, and/or altering the chemical composition of seminal fluid giving less protection for the ejaculated sperm cells.…”
Section: Sperm-fish Studies Of Alcoholmentioning
confidence: 99%
“…Tanto el etanol como el acetaldehído, pueden afectar los patrones de metilación de ADN mediante la alteración de la actividad DNMTs. Así, algunas investigaciones descubrieron que el acetaldehído puede inhibir la actividad de DNMT in vitro (Garro et al, 1991) y que el alcohol reduce los niveles de mARN de DNMTs en ratas tratadas con alcohol durante 9 semanas (Bielawski et al, 2002). Del mismo modo, los estudios en humanos han encontrado que los niveles de mARN de DNMT3a y DNMT3b se redujeron significativamente en pacientes con alcoholismo crónico en comparación con los sujetos control sanos (Bönsch et al, 2006).…”
Section: Metilación Del Adnunclassified